2012
DOI: 10.1093/icvts/ivs339
|View full text |Cite
|
Sign up to set email alerts
|

Retrosternal goiter located in the mediastinum: surgical approach and operative difficulties

Abstract: Most retrosternal goiters are situated in the anterior mediastinal compartment, but according to the literature, 10-15% are located in the posterior mediastinum. Although most of the anterior mediastinal goiters can be removed by a transcervical approach, posterior mediastinal goiters may require additional extracervical incisions. We report the case of a huge posterior mediastinal goiter extending from the neck retrotracheally beyond the aortic arch and azygous vein with crossover from the left to the right s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 4 publications
0
18
0
4
Order By: Relevance
“…RSG is usually contained within the anterior mediastinum, however, posterior mediastinal RSG occurs in 10-15% of cases [6]. Most RSG can be managed through a cervical incision although it has been suggested that RSG with a large proportion of mass in the posterior mediastinum carry a higher risk of sternotomy which is more technically challenging and traumatic [7].…”
Section: Discussionmentioning
confidence: 99%
“…RSG is usually contained within the anterior mediastinum, however, posterior mediastinal RSG occurs in 10-15% of cases [6]. Most RSG can be managed through a cervical incision although it has been suggested that RSG with a large proportion of mass in the posterior mediastinum carry a higher risk of sternotomy which is more technically challenging and traumatic [7].…”
Section: Discussionmentioning
confidence: 99%
“…3 of these cases (50%) developed hypoparathyroidism after a form of sternotomy. Still malignant transformation is equivalent in RG to those residing entirely in the neck [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of these goiters are amenable to transcervical thyroidectomy, a minority of patients may require sternotomy or thorachotomy extending into the posterior mediastinum and retrovascular space. However, overall number of complications associated with this approach is higher than that seen with the transcervical approach 4 . Lateral thoracotomy cannot achieve good exposure for bilateral posterior retrovascular, recurrent goiter and especially their malignant forms.…”
Section: Introductionmentioning
confidence: 96%
“…However, overall number of complications associated with this approach is higher than that seen with the transcervical approach. 4 Lateral thoracotomy cannot achieve good exposure for bilateral posterior retrovascular, recurrent goiter and especially their malignant forms. Another advantage of sternotomy is that during any vascular injury surgeon can easily control this problem and if necessary can start cardiopulmonary bypass.…”
Section: Introductionmentioning
confidence: 99%